Epidemiological investigation and genetic evolutionary analysis of PRRSV-1 on a pig farm in China - Li, Chao; Xu, Hu; Zhao, Jing; Gong, Bangjun; Sun, Qi; Xiang, Lirun; Li, Wansheng; Guo, Zhenyang; Li, Jinhao; Tang, Yan-dong; Leng, Chaoliang; Peng, Jinmei; et al. (Frontiers in Microbiology, 2022)
Porcine Reproductive and Respiratory syndrome virus (PRRSV) has brought serious economic losses to pig industry. PRRSV-1 have existed in China for more than 25 years. The prevalence and features of PRRSV-1 on Chinese farms are unclear. We continuously monitored PRRSV in a pig farm with strict biosafety measures in Henan Province, China, in 2020. The results showed that multiple types of PRRSV coexisted on this single pig farm. PRRSV-1 was one of the main circulating strains on the farm and was responsible for infections throughout nearly the entire epidemic cycle. Phylogenetic analysis showed that PRRSV-1 isolates from this pig farm formed an independent branch, with all isolates belonging to BJEU06-1-like PRRSV. The analysis of selection pressure on ORF5 on this branch identified 5 amino acids as positive selection sites, indicating that PRRSV-1 had undergone adaptive evolution on this farm. According to the analysis of ORF5 of PRRSV-1 on this farm, the evolutionary rate of the BJEU06-1-like branch was estimated to be 1.01 × 10−2 sites/year. To further understand the genome-wide characteristics of PRRSV-1 on this pig farm, two full-length PRRSV-1 genomes representative of pig farms were obtained. The results of amino acid alignment revealed that although one NSP2 deletion was consistent with BJEU06-1, different new features were found in ORF3 and ORF4. According to the above results, PRRSV-1 has undergone considerable evolution in China. This study is the first to report the prevalence and characteristics of PRRSV-1 on a large farm in mainland China, which will provide a reference for the identification and further prevention and control of PRRSV-1. Keywords: PRRSV-1, first detection, main epidemic strain, Chinese pig farm, evolution and genetic diversity